Pendampingan Pengendalian Biaya dan Pelaporan Keuangan Pesantren di Majelis Ulumus Syar’i (MUS) Jawharul Falah Banyuwangi - Sugeng Hartanto; Berlina Yudha Pratiwi; Fachmi Reza (Indonesian Journal Publisher, 2022)
Islamic boarding schools are able to break through the backwardness of society into a social order that has an established economic capital. Islamic boarding schools need financing to support their survival in order to undergo a cycle and continue to develop like other institutions. The importance of the role of financing requires a financing management strategy. The Council of Ulumus Syar'i (MUS) Jawharul Falah has a goal to be achieved, has the resources and cannot be separated from that are the costs incurred from its development activities as well as financial reports as accountability and sources of development information. The implementation of this service activity is carried out using several stages of the method, namely; field survey, discussion, training and practice. Result, 80% The analysis of financing control strategy is based on two things, namely: financing control strategy in the form of Prosocial-based Financing Control and Manpower Contribution Strategy as an effort to control costs. Financial reports are prepared manually or computerized.